The role of exercise-induced short-chain fatty acids in the gut–muscle axis: implications for sarcopenia prevention and therapy - Fang, Junyi; Yan, Weiyi; Sun, Xuao; Chen, Jun (Frontiers in Microbiology, 2025)
Sarcopenia is an age-related syndrome characterized by a progressive loss of skeletal muscle mass and function, with its prevalence increasing annually and severely compromising the quality of life in older adults. The pathogenesis of sarcopenia is complex and closely associated with gut microbiota dysbiosis. Emerging evidence suggests that short-chain fatty acids (SCFAs), the main metabolites produced by the gut microbiota, act as key mediators linking gut microbes to skeletal muscle health, a relationship referred to as the gut–muscle axis. SCFAs not only regulate muscle protein metabolism and inflammatory responses but also improve skeletal muscle insulin sensitivity and mitochondrial function, thereby playing a crucial role in maintaining muscle health. Notably, exercise has been shown to increase the abundance of SCFA-producing bacteria in the gut of older adults, thereby elevating circulating SCFA levels. This review summarizes the effects of different exercise modalities on SCFA-producing gut microbiota and circulating SCFA levels in older adults. Furthermore, it discusses the potential mechanisms through which exercise-induced SCFAs contribute to the prevention and management of age-related sarcopenia, thereby providing new insights and scientific references for exercise-based strategies to prevent and treat this condition.